2011
DOI: 10.5851/kosfa.2011.31.3.325
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Loci and Candidate Genes Affecting Fatty Acid Composition in Cattle and Pig

Abstract: Investigations into fatty acid composition in meats are becoming more important due to consumer demand for high quality healthy food. Marker-assisted selection has been applied to livestock to improve meat quality by directly selecting animals for favorable alleles that affect economic traits. Quantitative trait loci affecting fatty acid composition in cattle and pigs were investigated, and five candidate genes (ACACA, FASN, SCD, FABPs, and SREBP-1) were significantly associated with fatty acid composition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Similar results were observed in another study using an Italian Duroc breed ( Davoli et al, 2012 ). Previous studies have reported that the FASN gene was involved in the synthesis of fatty acids ( Kim et al, 2011 ; Maharani et al, 2011 ). In this study, the AA genotype of the FSAN gene increased the backfat thickness of Duroc breed.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were observed in another study using an Italian Duroc breed ( Davoli et al, 2012 ). Previous studies have reported that the FASN gene was involved in the synthesis of fatty acids ( Kim et al, 2011 ; Maharani et al, 2011 ). In this study, the AA genotype of the FSAN gene increased the backfat thickness of Duroc breed.…”
Section: Resultsmentioning
confidence: 99%
“…Given the importance of consumer acceptability, the qualification of genetic markers for economically important traits such an intramuscular fat content should be intensively studied and implemented [20]. In the present study, we analysed three potential genetic markers within genes FASN, SCD and ACACA strongly associated with lipid metabolism [30]. The investigation included different production traits with particular emphasis on fat content.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Sakuma et al [60] reported medium to high heritability estimates of 0.48 to 0.85 for six out of the eight fatty acids analysed. Therefore, there is an increased research interest in breeding, selecting and producing farm animals with desirable fatty acid composition [62].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the composition of fatty acids stored in the fat depots mirror the action of SCD on fatty acids substrates [77]. The enzyme SCD catalyses the desaturation of SFA and MUFA by inserting a cis-double bond in the delta (∆) 9 position of SFA substrates, with a higher preference for palmitic acid and stearic acid substrates transformed into palmitoleic acid and oleic acid, respectively [62,77,78]. Nucleotide substitution of C with T identified in the fifth exon of bovine SCD gene at the 878 CDS causes the replacement of the amino acid alanine with valine [37].…”
Section: Stearoyl-coa Desaturase Gene Polymorphismsmentioning
confidence: 99%